Preeti Shenoy’s Portrayal of New Woman in It Happens for a Reason - PINKI YADAV (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Preeti Shenoy is a well renowned writer among the top five highest selling authors in India. She has been awarded the Academia Award for Business Excellence by the New Delhi Institute of Management. She has also given lectures in many educational institutions including IIT’s and IIM’s and corporate organisations such as KPMG, Infosys and Accenture. Her works include 34 Bubblegums and Candies, Life is What You Make It, Tea for Two and a Piece of Cake, The Secret Wishlist, The One You Can not Have, It Happens for a Reason, Love, Kisses and All Things Warm,Why We Love The Way We Do, Its All in the Planets, A Hundred Little Flames, Love A Little Stronger, The Rule Breakers, Wake Up, Life is Calling, and The Magic Mindset: How to Find Your Happy Place. Shenoy depicts her women characters bold, independent, and strong woman. Trisha, Nidhi, Sujata, Mary in Its All in the Planets and Vipasha Mishra in It Happens for a Reason are such examples. Trisha wants to live life according to her own wish. She does not like possessive nature of Aniket. Nidhi follows her own dreams and takes interest in blogging and pottery. Vipasha Mishra gives birth to a son out of wedlock and rearshim single handedly. And Tea for Two and a Piece of Cake is a story of Nisha who is a girl- next door with an average appearance and plum and her life is far from perfect. But she learns live life according to her own wish.